Globalization of the World Economy: What Happened in 1985? - Jörn Kleinert (Kiel Institute of World Economics (IfW), 2000)
This paper brings forward a three-country model to analyze the internationalization process in the age of globalization. It is shown that investment of one company increases not only the incentive to invest in another country for every national competitor but for third country's companies as well. That results from the adjustment of the host country's companies which react to their shrinking market share by reducing output and raising the price of their goods. Some host country's companies exit the market. The results are used to explain the surge of foreign direct investment since the mid-1980s.
Keywords: F12; F21; F23; 330; general equilibrium; globalization; multinational enterprises; Direktinvestition; Multinationales Unternehmen; Globalisierung; Standorttheorie; Mehr-Länder-Modell; Mehr-Sektoren-Modell; Allgemeines Gleichgewicht; Theorie